2007
DOI: 10.1088/0268-1242/23/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

Hall mobility and electron trap density in GaAsN grown by liquid phase epitaxy

Abstract: The Hall mobility of GaAsN layers grown by liquid phase epitaxy (LPE) is studied as a function of the nitrogen content in the material. It is observed that the parameter decreases with increasing nitrogen in the layer, in agreement with earlier theoretical predictions assuming scattering of electrons in nitrogen-related defects. It is also found that the decrease in mobility is accompanied by a corresponding increase in the density of electron traps, believed to originate from different configurations of nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…where e is the electron charge, µ e = 300 cm 2 Vs −1 , and µ hh = 50 cm 2 Vs −1 [81][82][83][84][85][86] are the electron, light hole and heavy hole mobilities. In contrast to equation ( 2), the exact Drude expression for the longitudinal conductivity contain magnetic field-dependent terms.…”
Section: Photoluminescence and Pcmentioning
confidence: 99%
“…where e is the electron charge, µ e = 300 cm 2 Vs −1 , and µ hh = 50 cm 2 Vs −1 [81][82][83][84][85][86] are the electron, light hole and heavy hole mobilities. In contrast to equation ( 2), the exact Drude expression for the longitudinal conductivity contain magnetic field-dependent terms.…”
Section: Photoluminescence and Pcmentioning
confidence: 99%
“…Despite years of extensive studies only a very limited effort has been directed towards understanding of the transport properties of the GaNAs alloy system [8][9][10][11][12][13][14][15]. It has been shown that mobility in the In y Ga 1-y N x As 1-x is limited mainly by two scattering mechanisms: the band broadening scattering (BBS) and the random field scattering (RFS) [3].…”
mentioning
confidence: 99%